Limited Effect of 60-Days Strict Head Down Tilt Bed Rest on Vascular Aging - Möstl, Stefan; Orter, Stefan; Hoffmann, Fabian; Bachler, Martin; Hametner, Bernhard; Wassertheurer, Siegfried; Rabineau, Jérémy; Mulder, Edwin; Johannes, Bernd; Jordan, Jens; Tank, Jens (Frontiers in Physiology, 2021)
Background. Cardiovascular risk may be increased in astronauts after long term space flights based on biomarkers indicating premature vascular ageing. We tested the hypothesis that 60 days of strict 6° head down tilt bed rest (HDTBR), an established space analogue, promotes vascular stiffening and that artificial gravity training ameliorates the response. Methods. We studied 24 healthy participants (8 women, 24 - 55 years, BMI = 24.3 ± 2.1 kg/m2) before and at the end of 60 days HDTBR. 16 subjects were assigned to daily artificial gravity. We applied echocardiography to measure stroke volume and isovolumetric contraction time (ICT), calculated arterial compliance (stroke volume/pulse pressure), and assessed aortic distensibility by MRI. Furthermore, we measured brachial-femoral pulse wave velocity (bfPWV) and pulse wave arrival times in different vascular beds by blood pressure cuffs and photoplethysmography. We corrected arrival times for ICT (cPAT). Results. In the pooled sample, diastolic blood pressure (+8 mmHg, p < 0.001), heart rate (+7 bpm, p = 0.002) and ICT (+8 ms, p = 0.036) increased during HDTBR. Stroke volume decreased by 14 ml (p = 0.001). bfPWV, arterial compliance, aortic distensibility and all cPAT remained unchanged. Aortic area tended to increase (p = 0.05). None of the parameters showed significant interaction between HDTBR and artificial gravity training. Conclusion. 60 days HDTBR, while producing cardiovascular deconditioning and cephalad fluid shifts akin to weightlessness, did not worsen vascular stiffness. Artificial gravity training did not modulate the response.